Negative and positive incremental forming: Comparison by geometrical, experimental, and FEM considerations. Issue 5 (4th April 2017) - Formisano, A.; Boccarusso, L.; Capece Minutolo, F.; Carrino, L.; Durante, M.; Langella, A.
ABSTRACT: This study compares negative incremental forming (NIF) and positive incremental forming (PIF) processes by geometrical considerations, finite element method (FEM) analyses, and experimental evaluations. Conical frusta were manufactured starting from AA5052H19 aluminum alloy sheets using both techniques. The processes were also simulated with LS-DYNA software and a close correlation between the experimental and numerical results was observed. The analysis of forming forces, forming limit diagrams (FLDs), and sheets thinning highlights that the PIF technique allows one to reach higher formability and geometrical accuracy. Finally, the differences in terms of surface quality were also discussed.